Modelling a legal framework on liability for haulage of goods by road / Anas Afandi Ahmad Apandi - Ahmad Apandi, Anas Afandi (2020)
The haulage industry in Malaysia is expanding. Efforts poured into expanding the industry are undeniable. Stakeholders with interests contribute to the expansion of the industry through innovation, technological evolutions and revolution. Haulage industry as we see today is comparatively more advanced in all areas compared to the yesteryears. This research addresses the notion of implementing a statutory legal framework as a standard to address liability for haulage of goods by road, thus enhance the duty of care of stakeholders in the industry. Methodologically, this research uses exploratory design based on qualitative technique. Information gathered derives from doctrinal, socio-legal and comparative legal research. The data gathering method acts as a knowledge acquisition database to support the creation of the model legal framework. Findings of the research show that there is mix practice by haulier, haulage associations and international haulage and haulage related bodies(the practice differs from one stakeholder with the other). Currently, the bargaining power of the interested party dictates the result of the haulage agreement. Through a legal framework, discrepancies of bargaining power would be minimised and each stakeholder irrespective of their bargaining power would have a reasonable amount of rights in their agreement. Since this research is an exploratory work, it would focus mainly on the idea of the establishment of a legal framework to regulate haulage liability of parties involved. This research is executed to address the legal needs of stakeholders involved in the industry. Currently, liability framework implemented by hauliers vary from each other; there are advantage and disadvantage of this customary practice. Having a nonstandardised liability framework increases the use of bargaining power by parties involved. This benefits those with high bargaining power as they are able to dictate the terms of the agreement. However, those with lesser bargaining power may not be able to obtain reasonable rights and benefit to protect themselves in haulage transaction. Information obtained in this research would act as a guide and possibly open further discussions on liability framework involving haulage of goods by road.